Improving safety climate and behavior through a multifaceted intervention: Results from a field experiment - Bronkhorst, Babette; Tummers, Lars; Steijn, Bram (Safety science, 2018)
•A multifaceted safety climate intervention includes safety agents and activities at different organizational levels.•The multifaceted safety climate intervention was tested in a field experiment in health care.•Safety climate and -behavior improved significantly through the multifaceted intervention.•The implementation process proved to be important for intervention effectiveness. Interventions aimed at increasing priority for employee safety could lead to better safety climate and safety behavior of employees. However, current studies reporting on safety climate interventions lack diversity in contexts and settings, they focus mainly on supervisors and do not take into account the implementation process of the intervention. We aim to add to the safety literature by testing the effects of a multifaceted safety climate intervention using a field experimental design. We analyzed data of 520 health care employees in five organizations and studied the effects of the implementation process. Results showed that safety climate and behavior scores were significantly higher at post-intervention among the intervention group as compared to the control group, while there were no differences pre-intervention. Results also showed that within the intervention group, employees who experienced more positive changes to work procedures and positive attitudes and actions of their supervisor towards the intervention experienced higher post-intervention safety climate and safety behavior. This study presents a new, multifaceted safety climate intervention strategy that can be useful for improving safety climate and safety behavior. It also shows the importance of the implementation process when conducting safety climate interventions.